Le Petit Machiavellian Prince: Effects of Latent Toxoplasmosis on Political Beliefs and Values - Kopecky, Robin; Příplatová, Lenka; Boschetti, Silvia; Talmont-Kaminski, Konrad; Flegr, Jaroslav (Evolutionary psychology, 2022)
Humans infected by Toxoplasma gondii express no specific symptoms but manifest higher incidence of many diseases, disorders and differences in personality and behavior. The aim of this study was to compare the political beliefs and values of Toxoplasma-infected and Toxoplasma-free participants. We measured beliefs and values of 2315 responders via an online survey (477 Toxoplasma-infected) using the Political Beliefs and Values Inventory (PI34). This study showed Toxoplasma-infected and Toxoplasma-free participants of our cross-sectional study differed in three of four factors of PI34, scoring higher in Tribalism and lower in Cultural liberalism and Anti-Authoritarianism. We found sex differences in political beliefs associated with Toxoplasma infection. Infected women scored higher in tribalism and lower in cultural liberalism, compared with the Toxoplasma-free control group, while infected men scored higher in economic equity. These results fit with sexual differences in behavior and attitude observed after toxoplasmosis infection. Controlling for the effect of worse physical health and mental health had little impact, suggesting that impaired health did not cause these changes. Rather than adaptation to prevalence of parasites, as suggested by parasite-stress theory, the differences might be side-effects of long-term mild inflammatory reaction. However, to get clear picture of the mild inflammation effects, more research focused on different infectious diseases is needed.
Keywords: parasite threat; Female; Personality; Toxoplasmosis; stress; ženské pohlaví; průřezové studie; pathogen avoidance; lidé; Toxoplasma; osobnost; Sexual Behavior; sexuální chování; Cross-Sectional Studies; Toxoplasma gondii; Male; manipulation hypothesis; toxoplazmóza; political beliefs; mužské pohlaví; infectious diseases; Humans